An Investigation of Teachers’ Roles in Implementing Project-Based Learning in Elementary Education - Rahmadila, Defitri; Purnawarman, Pupung; Setyarini, Sri (International Journal of Language Teaching and Education, 2026)
Understanding the right way to effectively implement Project-Based Learning (PBL) in classroom situations while overcoming challenges such as student engagement in the classroom might be a huge issue for teachers. This research explores the experiences, perceptions, and challenges of an elementary school teacher implementing Project-Based Learning (PBL) in their classroom. Using a qualitative approach within the framework of Vygotsky’s theory on socio-cultural, the study focuses on one teacher selected through purposive sampling based on their experience with PBL. Data collection involves semi-structured interviews to understand the teacher’s strategies, challenges, and perceptions. The findings reveal that teachers perceive themselves primarily as facilitators, emphasizing their role in creating a supportive learning environment that fosters student engagement and enhances learning outcomes. While the study highlights the positive impacts of PBL on student collaboration and critical thinking, it also identifies potential obstacles, such as time management and diverse student needs. Additionally, the research suggests the necessity for further investigation into the long-term effects of PBL on student development, as this aspect was not fully addressed in the current study.